FIQIH PERADABAN PESANTREN: MANAJEMEN PENDIDIKAN PESANTREN, SIYASAH DAN NEGARA BANGSA DALAM MEMBANGUN PERADABAN MAJU INDONESIA - Ahmad Halid; Muhammad Ilyas; Elga Yanuardianto; Anis Rofi Hidayah; Maria Ulfa (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2024)
This article examines and reveals very interesting things about the Islamic jurisprudence of Islamic boarding school educational civilization: Education, Siyasah and the Nation State. This topic is actually very interesting among the Nahdlatul Ulama Islamic boarding school, because it is a big BPNU project to commemorate the past century of NU (2022, 2023) and empower NU for a glorious and advanced Indonesian nation. The research method uses a qualitative approach and deepens historical and demographic data. The results of this research are that nations are groups (Madurese, Javanese, Balinese, Bawean, Dayak, etc.) gathered in an area that has diversity (pluralism) consisting of various religions, cultures, tribes, races, groups, languages, islands, ethnicities and others that occupy the country of Indonesia. Islamic boarding school civilization jurisprudence: siyasah and the nation The state is part of the muamalat fiqh for the civilization of the nation. The Indonesian State, using the Ta'ayusiyah State, is a symbiotic state or (ÃƒËœÃ‚ÂªÃƒâ„¢Ã†â€™ÃƒËœÃ‚Â§Ãƒâ„¢Ã‚ÂÃƒâ„¢Ã¢â‚¬Å¾Ãƒâ„¢Ã…Â ÃƒËœÃ‚Â© ÃƒËœÃ‚Â¯Ãƒâ„¢Ã‹â€ Ãƒâ„¢Ã¢â‚¬Å¾ÃƒËœÃ‚Â©) separate state and religion, but the two have a close, inseparable relationship. to give its influence, the state needs religion, religion needs the state